2009
DOI: 10.1016/j.neuroimage.2008.12.062
|View full text |Cite
|
Sign up to set email alerts
|

Reduced prefrontal and temporal processing and recall of high “sensation value” ads

Abstract: Public service announcements (PSAs) are non-commercial broadcast ads that are an important part of televised public health campaigns. “Message sensation value” (MSV), a measure of sensory intensity of audio, visual, and content features of an ad, is an important factor in PSA impact. Some communication theories propose that higher message sensation value brings increased attention and cognitive processing, leading to higher ad impact. Others argue that the attention-intensive format could compete with ad's mes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 52 publications
11
91
0
Order By: Relevance
“…One forced-exposure study found better performance on a recognition task and on psychophysiological measures of central cognitive processing after exposure to more extreme loss-framed messages than after exposure to less extreme and gain-framed messages 29. One study identified an advantage for low MSV on accuracy and response time,28 while another forced-exposure study found the impact of MSV on self-efficacy and beliefs depended on the sensation seeking level of participants 36. This study also found there was no effect of argument strength on beliefs and intentions 36.…”
Section: Resultsmentioning
confidence: 99%
“…One forced-exposure study found better performance on a recognition task and on psychophysiological measures of central cognitive processing after exposure to more extreme loss-framed messages than after exposure to less extreme and gain-framed messages 29. One study identified an advantage for low MSV on accuracy and response time,28 while another forced-exposure study found the impact of MSV on self-efficacy and beliefs depended on the sensation seeking level of participants 36. This study also found there was no effect of argument strength on beliefs and intentions 36.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, researchers are attempting to investigate the signs of the brain activity correlated with an increase of attention, memory, and emotional engagement during the observation of commercial advertisements [18,22]. In fact, indirect variables of emotional processing could be gathered by tracking variations of the activity of specific anatomical structures linked to the emotional processing activity in humans, such as the pre-and frontal cortex (PFC and FC, respectively, [11]).…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have found interactions where the theoretically predicted effects of a given message variable are conditional upon other variables (Kang, Cappella, & Fishbein, 2006;Lang & Yegiyan, 2008;Langleben et al, 2009;. Specifically, two important message features in many persuasion theories are (1) the strength of arguments within the message, and (2) the degree to which a message elicits physiological arousal.…”
mentioning
confidence: 99%